Utilisation of Fruit Waste for Bio-Electricity Production with Microbial Fuel Cell - Sahu, Omprakash; Kaur, Supreet (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
The prodigious energy consumption in conjunction with the fleet growth of population, made the need to develop energy resources. Energy sources available have been classified into fossil fuels, nuclear and renewable energy sources based on their mode of origin and reliability. Microbial Fuel Cell is one the advancement in the future of environment protection. The technology will be closer to realistic applications with the introduction of highly efficient electrode materials and catalysts to decrease production costs. The primary components of fuel cells are electrodes i.e. anode and cathode. The anode is an electrode that induces oxidation and loss of electrons. The cathode is where there is reduction and the production of electrons. Anode surface fuel oxidation produces electrons and oxidized by-products. The electrons later pass through an outside circuit to the cathode. The experiment with biomass of organic fruit waste the result comes around 80-250 mV. This study shows that monosaccharide, disaccharides and polysaccharides present into fruits wastes are frequently used in the metabolic routes of the high microbial populations for the bioelectricity production. The new bridge introduced as sulphuric acid works effectively when operated in microbial fuel cell. How to cite this article:  Kaur S, Sahu O. Utilisation of Fruit Waste for Bio-Electricity Production with Microbial Fuel Cell. J Adv Res Alt Energ Env Eco 2021; 8(2): 9-14.